The molecular basis of the genesis of basal tone in internal anal sphincter - Cheng-Hai Zhang (Nature Portfolio, 2016)
The molecular basis of the basal tone generated by internal anal sphincters (IAS) is largely unknown. Here, the authors show that the tone arises from a global rise in intracellular Ca2+ in smooth muscle cells via a Ryanodine receptor-TMEM16A-L-type Ca2+channel-MLC kinase pathway, suggesting a potential therapy for IAS motility disorders.